Humanitarian commitment: Indonesia's policy on refugees’ rights to health - R Yahdi Ramadani; Aktieva Tri Tjitrawati; Mochamad Kevin Romadhona (Healthcare in Low-resource Settings, 2025)
Refugees have faced many challenges, including access to housing, education, and social and health services. International conventions regulate human rights that all civilized countries must obey, starting from the Declaration of Human Rights, the International Covenant on Civil and Political Rights and Indonesia, the International Covenant on Economic, Social and Cultural Rights and others recognized internationally and nationally. Indonesia, although not a state party to the 1951 Convention and 1967 Protocol on refugees, must pay attention to how to pay attention to foreigners, especially refugees in its territory. In providing protection and fulfillment of rights, Indonesia must refer to one of the international principles in providing needs to foreigners, namely the International Minimum Standards and National Treatment Standards.